Dorothy Hodgkin Lecture 2010. From hype to hope? A journey through the genetics of Type 2 diabetes. - McCarthy, M (2011)
Recent advances in genetic analysis have enabled researchers to perform genome-wide surveys for common DNA sequence variants associated with risk of Type 2 diabetes and related traits. Over the past 4 years, these endeavours have extended the number of proven Type 2 diabetes-susceptibility loci from a handful to the current total of over 40. Each of these loci provides an opportunity to uncover insights into the biology of glucose regulation and the pathogenesis of Type 2 diabetes, insights which should support clinical translation to identify novel ways of treating and preventing disease. Here, I describe (i) progress in identification of diabetes-susceptibility loci; (ii) biological insights that have been gained in the relatively short period since these loci were discovered; and (iii) the challenges that need to be addressed if we are to maximize the translational benefits of this research.